Gross anatomical structures of the skull of chital - Parmar, M L; Shrivastav, A B (The Indian Journal of Animal Sciences, 2011)
The frontal surface of the skull of chital (Axis axis) was formed by squamous part of the occipital, parietal, frontal, nasal and incisive bones. The interparietal bone was not traceable. In the maceratcd skull, the frontal surface below the orbit presented a triangular opening (lacrimal fissure). The facial tuberosity and infraorbital foramen were present above the third and fIrst cheek tooth respectively. The incisive bone was devoid of palatine process.